Respuesta :
Subtract x^2 from both sides
x^2 + 3x - 7 = 5x + 39
Subtract 5x from both sides
x^2 - 2x - 7 = 39
Add 7 to both sides
x^2 - 2x = 46
Complete the square by adding (b/2)^2 to both sides, b = ( -2)
(-2/2) = -1, then square that (-1)^2 = 1
x^2 - 2x + 1 = 46 + 1
Simplify the expression by factoring
(x - 1)^2 = 47
Take square root on each side
x - 1 = (sqrt (47))
Solve for x
x = 1 + (sqrt (47))
Since 47 is prime, 47 cannot be broken down by the square root and this is the answer to your problem.
x^2 + 3x - 7 = 5x + 39
Subtract 5x from both sides
x^2 - 2x - 7 = 39
Add 7 to both sides
x^2 - 2x = 46
Complete the square by adding (b/2)^2 to both sides, b = ( -2)
(-2/2) = -1, then square that (-1)^2 = 1
x^2 - 2x + 1 = 46 + 1
Simplify the expression by factoring
(x - 1)^2 = 47
Take square root on each side
x - 1 = (sqrt (47))
Solve for x
x = 1 + (sqrt (47))
Since 47 is prime, 47 cannot be broken down by the square root and this is the answer to your problem.
Answer:
[tex]x=1\pm\sqrt{47}[/tex]
Step-by-step explanation:
We have been given an equation [tex]2x^2+3x-7=x^2+5x+39[/tex]. We are asked to find the solution for our given equation.
[tex]2x^2+3x-7=x^2+5x+39[/tex]
[tex]2x^2-x^2+3x-7=x^2-x^2+5x+39[/tex]
[tex]x^2+3x-7=5x+39[/tex]
[tex]x^2+3x-5x-7-39=5x-5x+39-39[/tex]
[tex]x^2-2x-46=0[/tex]
Using quadratic formula, we will get:
[tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
[tex]x=\frac{-(-2)\pm\sqrt{(-2)^2-4(1)(-46)}}{2(1)}[/tex]
[tex]x=\frac{2\pm\sqrt{4+184}}{2}[/tex]
[tex]x=\frac{2\pm\sqrt{188}}{2}[/tex]
[tex]x=\frac{2\pm2\sqrt{47}}{2}[/tex]
[tex]x=1\pm\sqrt{47}[/tex]
Therefore, the solutions for our given equation are [tex]x=1\pm\sqrt{47}[/tex].